2008
DOI: 10.1007/s00213-008-1396-0
|View full text |Cite
|
Sign up to set email alerts
|

The adenosine A2A antagonist MSX-3 reverses the effort-related effects of dopamine blockade: differential interaction with D1 and D2 family antagonists

Abstract: Rationale-Brain dopamine (DA) participates in the modulation of instrumental behavior, including aspects of behavioral activation and effort-related choice behavior. Rats with impaired DA transmission reallocate their behavior away from food-seeking behaviors that have high response requirements, and instead select less effortful alternatives. Although accumbens DA is considered a critical component of the brain circuitry regulating effort-related choice behavior, emerging evidence demonstrates a role for aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
53
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 79 publications
10
53
0
Order By: Relevance
“…Though previous work has shown that MSX-3 had no effect of FR5/chow feeding choice performance when administered on its own (Farrar et al 2007), co-administration of MSX-3 significantly reversed the behavioral effects of IL-1β injections, restoring the baseline behavioral pattern by increasing lever pressing and decreasing chow intake in IL-1β-treated rats. These results are consistent with previous research demonstrating that adenosine A 2A receptor blockade or genetic deletion can reverse the effort-related effects of DA antagonism and depletion (Farrar et al 2007, 2010; Worden et al 2009; Mott et al 2009; Salamone et al 2009; Nunes et al 2010; Pardo et al 2012). Furthermore, the present findings are consistent with reports showing that the adenosine A 2A antagonists can produce effects that are consistent with the behavioral profile of an antidepressant in rodents tested on the swim test or tail suspension task (El Yacoubi et al 2001; Hodgson et al 2009; Hanff et al 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Though previous work has shown that MSX-3 had no effect of FR5/chow feeding choice performance when administered on its own (Farrar et al 2007), co-administration of MSX-3 significantly reversed the behavioral effects of IL-1β injections, restoring the baseline behavioral pattern by increasing lever pressing and decreasing chow intake in IL-1β-treated rats. These results are consistent with previous research demonstrating that adenosine A 2A receptor blockade or genetic deletion can reverse the effort-related effects of DA antagonism and depletion (Farrar et al 2007, 2010; Worden et al 2009; Mott et al 2009; Salamone et al 2009; Nunes et al 2010; Pardo et al 2012). Furthermore, the present findings are consistent with reports showing that the adenosine A 2A antagonists can produce effects that are consistent with the behavioral profile of an antidepressant in rodents tested on the swim test or tail suspension task (El Yacoubi et al 2001; Hodgson et al 2009; Hanff et al 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, A 1 R and A 2A R are now recognized as major modulators of striatum function. Their relatively high degree of expression in the striatum, predominate post-synaptic location on medium spiny neurons, and antagonistic interaction with dopamine receptors are consistent with a role in motor control, instrumental learning, habit learning, working memory, reward, and motivation [76-85]. Thus, potential changes to A 1 R and A 2A R expression, related to reduced mRNA from running, may influence a number of striatum-involved cognitive modalities.…”
Section: Discussionmentioning
confidence: 94%
“…For example, a recent study demonstrated that blocking A 2A receptors, and hence, removing the adenosine 'brake', produces wakefulness (Lazarus et al, 2011). Antagonism of A 2A receptors also restores deficits in effort-related behaviors induced by D 2 receptor blockade Worden et al, 2009), suggesting that A 2A receptors are a tonic modulator of D 2 receptor expressing neurons within the striatum (Harper et al, 2006;Nagel et al, 2003). Our data provide further support that A 2A receptors exert tonic regulation of D 2 receptors and suggests that A 2A receptors are an important modulator of DA-mediated behavior (Farrar et al, 2010;Hakansson et al, 2006;Harper et al, 2006;Nagel et al, 2003;Weber et al, 2010).…”
Section: Discussionmentioning
confidence: 96%